Signs of Happiness on The Captions of Cinta Laura Kiehl’s Instagram - Saputri, Agustina Riska Eka; Mansyur, Agus Salim; Rusmana, Dadan (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
The semiotic phenomenon is known to be closely related in the field of communication. This research especially focuses on the semiosis process identified from Cinta Laura Kiehl’s Instagram captions as a famous celebrity in Indonesia. The semiotic sign relation is seen through her captions that do not only include the text but also a form of icon reflected through emoticons added in the captions. This study applied qualitative research method to present the data analysis. Moreover, this research also uses several guiding perceptions with the main theory of sign relation by Charles Sanders Peirce and the supporting perception of happiness by Martin Seligman. There are several results determined from this research. The first result shows that the symbol sign relations in Cinta’s Instagram captions are in the form of texts that conveyed meaning in the expression of happiness that Cinta shares based on her life. Moreover, the emoticons in her Instagram captions have the function to enhance the expressions and contexts that the symbol initially stands for. The second result shows that the signs of happiness from Cinta’s Instagram captions are divided into two main aspects of relationship and achievements. Thus, the sign relations in Cinta’s Instagram captions are used in conveying the expressions of happiness Cinta shares based on her life.